Economic Evaluation of Historical Tourist Attraction and Analysis of Its Affecting Factors using Multilevel Ordered Logistics Method (Case Study: Golan Historical Neighborhood of Hamadan) - Saeed Dehghan Khavari; Golnoush Jabbari; Seyed Hossein Mirjalili (اقتصاد باثبات)
Preservation and revitalization of historical neighborhoods is considered one of the necessities of urban tourism development as a valuable heritage from the past and a part of the historical identity of human societies, which leads to the vitality of the city in the direction of sustainable tourism development. Therefore, the urban tourism approach of historical neighborhoods is effective in preserving and revitalizing the historical context, as well as economic benefits and sustainable incomes. This article deals with determining the economic value of Golan historical neighborhood in Hamadan city. The research method is applied and descriptive-analytical. The statistical population of the research is the tourists of Golan historical quarter, which was randomly surveyed from 347 people in the form of a questionnaire. Also, by using 4 models and multi-level sequential logistic method, the factors and their effect on various types of payment tendencies have been calculated. Due to the tendency to pay at different levels, the use of this method can measure the effective factors with higher accuracy. Also, the error in the stated information, if any, has less effect on the output of the model in this method than normal regression. The results show that the willingness to make a one-time payment is 40 thousand tomans and the willingness to pay annually and also to protect and prevent its destruction in the form of a per capita tax is 24 thousand tomans. Also, interest in visiting historical neighborhoods, education and employment have been identified as the most important influencing factors. The results of the conditional one-time payment model also show that education, interest and the number of annual visits are the factors that influence the approval or rejection of the payment request of the set limit (35,000 Tomans).